The Loneliness Of Orphans In The Orphanage Based On Gender, Education Level And Personality Type - Noviyanti, Rezkika; Amienarti, Afifah; Ardiani, Rahma; Rachmawati, Depy Eka; Anganthi, Nisa Rachmah Nur (Prosiding University Research Colloquium, 2021)
The pandemic that occurred since 2019 caused a disruptive change in the pattern of human life demands the productivity of fatwas related to new things. This study aims to look more deeply at the sadd adz-dzari’ah method and its correlation in determining fatwas during the pandemic. The method used in this study is a qualitative method by holistically analyzing the object of research. The results of the study found that sadd adz-dzari’ah has a very important position in the process of determining the fatwa by Fatwa Council in Indonesia and become the most appropriate method for preventing mudhorot and achieving maslahah.